2011
DOI: 10.1111/j.1743-6109.2010.02049.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cavernous Expression of Transforming Growth Factor-β1 and Activation of the Smad Signaling Pathway Affects Erectile Dysfunction in Men with Spinal Cord Injury

Abstract: Introduction Transforming growth factor-β1 (TGF-β1) is implicated in bladder fibrosis after spinal cord injury (SCI) and in the fibrosis in the corpus cavernosum tissue after cavernous nerve injury. Aim We investigated the differential expression of TGF-β1 and the Smad transcription factor, the key molecule for the initiation of TGF-β-mediated fibrosis, in cavernous tissue from SCI patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…It has been hypothesized that cavernosal nerve damage, such as that after radical prostatectomy, is associated with hypoxia-induced activation of the TGF-β1/Smad signaling pathway in the corpus cavernosum, which further leads to fibrosis and loss of smooth muscle content in erectile tissue [6,7] . Results from the current study confirmed previous reports showing activation of the TGF-β1/Smad2 pathway and increased collagen content in CN-crushed rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that cavernosal nerve damage, such as that after radical prostatectomy, is associated with hypoxia-induced activation of the TGF-β1/Smad signaling pathway in the corpus cavernosum, which further leads to fibrosis and loss of smooth muscle content in erectile tissue [6,7] . Results from the current study confirmed previous reports showing activation of the TGF-β1/Smad2 pathway and increased collagen content in CN-crushed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Following phosphorylated, Smad2 translocates to the nucleus and regulates the transcription of TGF-β target genes. It has been reported that upregulation of the TGF-β1/Smad signaling pathway might play an important role in ED-associated cavernosal fibrosis [7,9] . As a result of this denervation and structural changes in erectile tissue, often severe and difficult-to-treat ED develops.…”
mentioning
confidence: 99%
“…Acute SCI permits phasic penile erection, and these sexual reflexes can be observed during several weeks in the rat without significant changes. 16 Shin et al 17 reported that apoptosis, collagen deposition, smooth muscle cell loss and fibrosis were increased in the corpus cavernoum tissue specimens obtained by percutaneous biopsy from 10 SCIinduced ED patients. The authors also suggested that the patients might benefit from early pharmacotherapy (PDE-5 inhibitors) to prevent this irreversible injury.…”
Section: Discussionmentioning
confidence: 99%
“…Sinirsel uyarımın kaybolduğu/azaldığı spinal kord ve periferik sinir lezyonlu erektil disfonksiyonlu olgularda süregen fibrozise yol açan kavernozal transforming growth faktör beta-1 (TGF-β1) yoğunluğu artmış bulunmuştur. [32] Spinal kord yaralanmalarında ejakulasyon işlevi de etkilenir. [12,33] Ejakulasyonun otonomik komponenti emisyon, somatik komponenti ekspulsiyondur (Şekil 2).…”
Section: Normal Erkek Cinsel Işleviunclassified
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Torakolomber bölge ile sakral merkezler arasındaki spinal kord lezyonlarında refleks ereksiyonlar görülürken psikojenik ereksiyon oluşmaz. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Ancak bu seviyede lezyonu olan olgularda psikojenik ereksiyonların da görülebildiği rapor edilmiştir. Bu durum torakolomber bölgenin altında paravertebral gongliyonlardaki parasempatiklerin normal kalması ve azalmış hipogastrik (sempatik) tonusa bağlı nöroplastite ile açıklanmıştır.…”
Section: Normal Erkek Cinsel Işleviunclassified